2023
DOI: 10.1021/acs.inorgchem.3c02868
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Rapid Detection of 4-Nitrophenol in River and Treated Industrial Wastewater by a Luminescent Lanthanide Metal–Organic Framework Sensor

Yang Yang,
Zhonghang Chen,
Chuya Fu
et al.

Abstract: Phenolic organic compounds are widely used industrial chemicals that exist extensively in the environment and have a significant impact on human health. 4-Nitrophenol (4-NP) is a typical phenolic organic compound found in aqueous environments. Efficient detection of 4-NP in wastewater is highly challenging due to the complexity of testing environmental samples. Herein, a luminescent lanthanide metal–organic framework (MOF) sensor based on the Eu3+ ion {[Eu­(HL)­(L)­(H2O)]·2H2O} n (EuMOF; H2L = 5-(4H-1,2,4-tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This is better than most previously reported CP-based fluorescent sensors for 4-NP (Table 4). 56–62 Compound 1 could be regenerated after washing several times with DMF; however, the fluorescence intensity of 1 decreased (Fig. S24†).…”
Section: Resultsmentioning
confidence: 99%
“…This is better than most previously reported CP-based fluorescent sensors for 4-NP (Table 4). 56–62 Compound 1 could be regenerated after washing several times with DMF; however, the fluorescence intensity of 1 decreased (Fig. S24†).…”
Section: Resultsmentioning
confidence: 99%
“…Forest decline has been attributed to these phytotoxic, cytotoxic, and mutagenic compounds as well. Nitrophenols are ubiquitous in the atmosphere, especially in urban areas, and in the environment due to anthropogenic emission, e.g. from combustion processes, dye industry, or pesticide hydrolysis. ,, Whereas para -nitrophenol (4-NP) occurs mainly as particles bound in clouds, a liquid phase enrichment of ortho -nitrophenol (2-NP), e.g. in fog and small cloud droplets, was measured .…”
Section: Introductionmentioning
confidence: 99%
“…from combustion processes, dye industry, or pesticide hydrolysis. 22 , 31 , 32 Whereas para -nitrophenol (4-NP) occurs mainly as particles bound in clouds, a liquid phase enrichment of ortho -nitrophenol (2-NP), e.g. in fog and small cloud droplets, was measured.…”
Section: Introductionmentioning
confidence: 99%
“…One such contaminant is para nitrophenol (PNP), an organic compound involved in the manufacture of pharmaceuticals like acetaminophen, textiles, plastics, synthetic dyes and herbicides among other applications (Maleki et al, 2022). It has been detected in industry wastewater and is toxic to aquatic life, humans and animals and thus has to be removed (Yang et al, 2023;Chen et al, 2017). Previous research has demonstrated greensynthesized AgNPs as a more sustainable and environmentally friendly alternative to conventional catalysts which utilize expensive chemicals and generate toxic by-products in the process (Rani et al, 2020;Shah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%